The Durability of The Enterprise Created by Resilience - Weronika TOSZEWSKA-CZERNIEJ (Communications of International Proceedings, 2023)
The aim of the article is to present the results of the project Employee at work of the future implemented in 2022 by a team of employees of the Faculty of Economic Sciences of the Koszalin University of Technology. The article is an attempt to verify the extremely changing realities of employees and assumes better prediction of trends and greater ability to adapt to the dynamically changing labor market. The main purpose of the article is to present the theoretical aspects of the resilience process and its importance for building the value of an organization. The article presents and discusses the developed model of organization's resilience, verification by showing the results of the research process allowing for a better understanding and use of the concept. The research concerned a sample of over 1,000 employees and included an analysis of the current situation in accordance with the Polish Classification of Activities (PKD) in the areas of industry, services, trade and construction, as well as an assessment of work processes, human potential and working conditions. The presented results regarding the individual stages of the process of building organizational resilience show the employee's assessment of the preparation of the areas of people and the process in accordance with the presented model. The results in the individual stages of the process indicate a positive assessment of the activities of Polish enterprises. This paper focuses on the changing role of people in an organization, leading to the organization's adaptive capacity thus increasing the organization's resilience to uncertainty.
Keywords: resilience; organization resilience